2008
DOI: 10.1080/01676830802352543
|View full text |Cite
|
Sign up to set email alerts
|

Facial Nerve Palsy: Anatomy, Etiology, Evaluation, and Management

Abstract: The ophthalmologist may be the first clinician to see a patient who presents with acute facial nerve palsy. Under such circumstances the ophthalmologist should make every effort to establish the underlying cause of the facial palsy and ensure that the patient's cornea is adequately protected. This article reviews the anatomy of the facial nerve, the varied disorders that may cause a facial palsy, a detailed evaluation of such a patient, and the various medical and surgical treatments available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 41 publications
0
66
0
2
Order By: Relevance
“…Unlike central FNP, in peripheral idiopathic FNPs imaging is not crucial for work-up or treatment in patients with typical clinical findings, as most patients recover within 3–6 months of onset [10]. Imaging is, therefore, only recommended to rule out neoplasms and other causes in patients with no response to initial treatment after 3 months or with progressive facial nerve paralysis [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike central FNP, in peripheral idiopathic FNPs imaging is not crucial for work-up or treatment in patients with typical clinical findings, as most patients recover within 3–6 months of onset [10]. Imaging is, therefore, only recommended to rule out neoplasms and other causes in patients with no response to initial treatment after 3 months or with progressive facial nerve paralysis [3, 4].…”
Section: Discussionmentioning
confidence: 99%
“…14 The results of MGD assessment in this study were similar to those from a previous study 1 ; however, the previous study showed no significant difference in Schirmer values between sides. 1 Reflexive hyperlacrimation due to exposure keratitis 6 and decreased lacrimal pump function 15 occasionally occur in patients with CN VII palsy. Although the severity of CN VII palsy was not examined, this may differ between the present and previous studies, 1 causing the discrepant finding in Schirmer test I.…”
Section: Discussionmentioning
confidence: 99%
“…Between the labyrinthine and tympanic segments lies the geniculate ganglion where the petrosal branches are given off. Lesions prior to the geniculate ganglion result in more severe ocular complications due to the lack of lacrimal secretions (Mavrikakis 2008 ) . In the tympanic segment, the nerve passes behind the cochleariform process against the medial wall of the cavum tympani, above and posterior to the oval window.…”
Section: Anatomymentioning
confidence: 99%